2019
DOI: 10.1039/c9ra02052g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel magnetic Caragana korshinskii biochar/Mg–Al layered double hydroxide composite and its strong adsorption of phosphate in aqueous solutions

Abstract: This study describes an optimized two-step electro-assisted modification process for the preparation of biochar modified with Fe3O4 and Mg–Al layered double hydroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 48 publications
4
29
1
Order By: Relevance
“…The irreversible desorption portion was attributed to specific adsorption that formed strong metal-P bonding. Compared with parallel studies [47,48], the repeated chemical desorption in this study didn't perform significant impair in performance and weight aspects of the modified materials, suggesting their strong reusability in the potential engineering practice.…”
Section: Regeneration Cycles and Continuous Flow Adsorption Testmentioning
confidence: 64%
“…The irreversible desorption portion was attributed to specific adsorption that formed strong metal-P bonding. Compared with parallel studies [47,48], the repeated chemical desorption in this study didn't perform significant impair in performance and weight aspects of the modified materials, suggesting their strong reusability in the potential engineering practice.…”
Section: Regeneration Cycles and Continuous Flow Adsorption Testmentioning
confidence: 64%
“…It can be clearly seen that CB has about six identical peak positions, which are located near 500-900, 1300-1400, 1600, 2300, 2800, and 3400 cm −1 . Viewing the spectrum data table [3,6,11,17,18,24], it was found that CB has -OH vibration absorption peak (3418 cm −1 ), and the C-H in alkanes are mainly vibration absorption peaks of methyl and methylene groups (2854-2966 cm −1 ), the fatty C-H and C=O groups (2280 cm −1 ), aromatic acids -COOH groups (1697 cm −1 ), amide stretching vibration -C=O group (1650 cm −1 ), NH 4 + group (1396 cm −1 ), the pyridine and indole of aromatic compounds (500-900 cm −1 ) groups. It shows that CB has rich functional groups on its surface.…”
Section: Ftirmentioning
confidence: 99%
“…The Q m values and the actual maximum adsorption capacity obtained by the experiments were significantly different. The difference is attributed to the limitations and errors of the model, which are reflected on the isothermal adsorption curve [4]. The R L values of NO 3 − are between 0 and 1, thus indicating a favorable adsorption process.…”
Section: Isotherms Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Qing Liang Cui et al 2019 [32] investigated magnetic biochar/Mg-Al layered double hydroxide composite and reported relatively higher adsorption capacity as compared to other magnetic adsorbents, with moderate 51.43% removal efficiency. Yan-Hong Jiang et al [33] loaded ZnAl-LDH on to modified banana straw biochar via a hydrothermal process and demonstrated significant improvement in phosphorus removal.…”
Section: Introductionmentioning
confidence: 99%